Ways to detect plagiarism in academic research - TABIRCA, Adina; RADU, Valentin (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 17 (2015): Annales Universitatis Apulensis Series Oeconomica, 2015)
Present environment seems to increase scientific production due to the fact that quantity is more important than quality. Therefore, researchers, professors and PhD students are obliged to proceed with the dissemination of individual or collective researches in order to quantify the number of published papers in various journals. As result, we are witnessing a boom of scientific papers, sometimes of dubious quality. In fact the excess number of publications led us think … How many of these papers are plagiarized and how it can be detected in any research paper? When a paper is considered plagiarized? How can we verify the originality of a research paper? Who can detect plagiarism? Can plagiarism be prevented? In order to respond to these questions we proceeded to a participant observation of specialty research papers registered at the level of   higher education institutions within two years. At the same time, we analyzed the flow of information available online about the current trend and associated interpretations in mass media of plagiarism phenomenon. Thus, we will use regional research methods, especially social sciences to analyze the paradigm and to allow discussions on a wide range that goes from complete refusal to validate the paradigm. To be able to formulate answers to the stated questions, we provided a case study on the results of original scientific papers accumulated at an educational institution, taking into account the range and level of education of paper’s author.